EDUKASI BAHAYA NARKOBA PADA GENERASI MUDA KARANG TARUNA KELURAHAN KALIANCAR DI MASA PANDEMI - Undari Nurkalis; Rahayu Setyaningsih (Universitas Borneo Tarakan, 2023)
Narcotics are substances or drugs that are natural, synthetic, or semi-synthetic which causes a loss of consciousness, hallucinations, and excitability. Excessive use of these drugs can cause addiction, decreased consciousness, changes in brain cells, decreased quality of life, and can even lead to death. During the COVID-19 pandemic, the challenges in handling and preventing drugs were higher and it can impact the difficult economic conditions that allow people to use drugs. The social impact of the pandemic has also led to increased inequality, poverty, and impaired mental health conditions that could encourage more people to use drugs. Drug abuse among adolescents increases. This community service aims to increase the knowledge of the young generation of youth groups in RW 07 Kaliancar Village about the dangers caused by drug use. This activity is carried out using the counseling method. Evaluation of counseling activities in this service can increase the knowledge of the younger generation about the dangers of drug use, both in the short term and in the long term.